2021
DOI: 10.1038/s41523-021-00283-z
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and molecular significance associated with STING signaling in breast cancer

Abstract: STING signaling in cancer is a crucial component of response to immunotherapy and other anti-cancer treatments. Currently, there is no robust method of measuring STING activation in cancer. Here, we describe an immunohistochemistry-based assay with digital pathology assessment of STING in tumor cells. Using this novel approach in estrogen receptor-positive (ER+) and ER- breast cancer, we identify perinuclear-localized expression of STING (pnSTING) in ER+ cases as an independent predictor of good prognosis, ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…However, pSTAT1 was not an independent prognostic marker in multivariate analysis. A previous study revealed that pnSTING is an independent predictor of favourable RFS in ER + breast cancer and is associated with immune cell in ltration and upregulation of immune checkpoints 15 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, pSTAT1 was not an independent prognostic marker in multivariate analysis. A previous study revealed that pnSTING is an independent predictor of favourable RFS in ER + breast cancer and is associated with immune cell in ltration and upregulation of immune checkpoints 15 .…”
Section: Discussionmentioning
confidence: 98%
“…The H scores (range from 0-200) were calculated by intensity (negative: 0; medium: 1; high: 2) multiplied by the percentage of cells in each group. As previously described, peri-nuclear STING (pnSTING) expression was evaluated by the percentage of positive cells as a proxy for activated STING 15 . The percentage of pnSTING-positive tumor cells was then scored semi-quantitatively.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Conversely, STING activation of noncanonical inflammatory pathways has been found to promote epithelial–mesenchymal transition and metastasis in cancers with high chromosomal instability that generate excessive dsDNA in the cytosol ( 74 ). It is possible that evasion or activation of dsDNA sensing pathways in tumors is largely shaped by specific tumor contexts, selective pressures, and immune editing that are not captured by reductionist models ( 48 , 69 , 70 , 75 , 76 , 77 , 78 ). Our work demonstrates that separate from specific tumor or immune selective factors, oncogenes autonomously downregulate T1IFN expression, causing direct and dramatic consequences to antiviral dsRNA sensors that are strong ISGs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to control (Ctr) cells, loss of Atg5 in ECs increased granular STING staining in the perinuclear regions, a hallmark of STING activation and signaling (Extended Data Fig. 4h) 40 .…”
Section: Autophagy Blunts the Nf-b And Cgas-sting Inflammatory Axis ...mentioning
confidence: 97%